1963
DOI: 10.1042/bj0870462
|View full text |Cite
|
Sign up to set email alerts
|

Control of Porphyrin Biosynthesis through a Negative-Feedback Mechanism. STUDIES WITH PREPARATIONS OF δ-AMINOLAEVULATE SYNTHETASE AND δ-AMINOLAEVULATE DEHYDRATASE FROM RHODOPSEUDOMONAS SPHEROIDES

Abstract: Succinyl-CoA was prepared by the method of Simon & Shemin (1953) and was used immediately. The values quoted for succinyl-CoA are based on the amount of CoA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
36
0

Year Published

1967
1967
1986
1986

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(42 citation statements)
references
References 25 publications
6
36
0
Order By: Relevance
“…Heme functions as an allosteric inhibitor and repressor of ALA synthase in photosynthetic bacteria (7,15,17), and it appears to act as a central regulator of bacteriochlorophyll synthesis in Rhodopseudomonas spheroides (17) by controlling the part of the pathway that is common to both heme and Chl formation. Because certain iron chelators have been found to induce accumulation of porphyrin and Mg-porphyrin Chl precursors while blocking heme synthesis in etiolated plant tissues (10,12,13), it has been proposed that heme may act to repress ALA formation in plants, thus regulating Chl precursor synthesis in a manner similar to the case in photosynthetic bacteria (8,10).…”
mentioning
confidence: 99%
“…Heme functions as an allosteric inhibitor and repressor of ALA synthase in photosynthetic bacteria (7,15,17), and it appears to act as a central regulator of bacteriochlorophyll synthesis in Rhodopseudomonas spheroides (17) by controlling the part of the pathway that is common to both heme and Chl formation. Because certain iron chelators have been found to induce accumulation of porphyrin and Mg-porphyrin Chl precursors while blocking heme synthesis in etiolated plant tissues (10,12,13), it has been proposed that heme may act to repress ALA formation in plants, thus regulating Chl precursor synthesis in a manner similar to the case in photosynthetic bacteria (8,10).…”
mentioning
confidence: 99%
“…In photosynthetic bacteria and in some heme-forming systems, ALA synthetase is a site of regulation of the pathway, being subject to feedback inhibition and induction (5,12).…”
mentioning
confidence: 99%
“…8-Aminolevulinic acid synthetase (ALAS) is the first and rate-limiting enzyme in the heme biosynthetic pathway (1), and Burnham and Lascelles have shown an inhibitory effect of hemin on this enzyme in the microorganism Rhodopseudomonas spheroides (2). Heady, Jacobs, and Deibel have demonstrated that the addition of hemin to cultures of Staphylococcus epidermidis inhibits the accumulation of coproporphyrin un-der conditions of impaired heme synthesis (3).…”
Section: Introductionmentioning
confidence: 99%